Consumer engagement and the perception of packaging information - Mruk-Tomczak, Dobrosława; Jerzyk, Ewa; Wawrzynkiewicz, Natalia (Olsztyn Economic Journal, 2019)
Packaging is an important factor influencing purchasing decisions, especially in the case of food products. Packaging draws the consumer’s attention and communicates with the consumer at a critical time in the purchasing process, providing information, while instructing and educating. The significance of the information varies depending on the product and on the information needs of the consumer stemming from his or her attitude. The level of consumer engagement in the purchase can significantly determine the perception of information – both emotional and factual - on the packaging. The aim of the article was to research the perception of the emotional content and factual information on the packaging of fruit juice, taking into account the level of consumer engagement in the purchase. It was assumed that high consumer engagement would result in greater visual attention to the product information. The tools used achieve the goal included eye-tracking and a questionnaire. The results have indicated that the level of consumer engagement in the purchase of fruit juice (purchase frequency and motivation) does not affect preferences regarding the type of the perceived information.